A Deep Scanning on Mild Mental Retardation Individual’s Language Acquisition and Development - Rachmi Retno Nursanti; Widyastuti Purbani (VELES Voices of English Language Education Society, 2022)
This research aims to investigate the language acquisition and development of a child with mild mental retardation in the 14th years old. The language acquisition is developed by appropriate treatment of caregivers including parent, family members, teachers, friends, and neighbors. Parent is the main caregiver that contributes language development of the child with mild mental retardation. The research uses qualitative approach in a case study as a research design. The results of this research show that the child got speech therapy in the 3rd years old and the parent provided facilities to develop language; such as story books, stationary, and gadgets. The child acquired four languages; Bahasa Indonesia, Javanese language, English language, and Arabic language since she went to school. Each language has different role in the child’s daily activities and communication. The schooling system contributed the child’s achievement academically and non-academically because she was studying at inclusive school with special teachers from psychology education background. In addition, neighborhood environment supported the child’s confidence to socialization.  Thus, this research is supposed to be a reference to the following researchers to discover more treatments to mentally retarded students in acquiring languages.